Animal Models of Cryptococcus neoformans in Identifying Immune Parameters Associated With Primary Infection and Reactivation of Latent Infection - Normile, Tyler G.; Bryan, Arielle M.; Del Poeta, Maurizio (Frontiers in Immunology, 2020)
Cryptococcus species are environmental fungal pathogens and the causative agents of cryptococcosis. Infection occurs upon inhalation of infectious particles, which proliferate in the lung causing a primary infection. From this primary lung infection, fungal cells can eventually disseminate to other organs, particularly the brain, causing lethal meningoencephalitis. However, in most cases, the primary infection resolves with the formation of a lung granuloma. Upon severe immunodeficiency, dormant cryptococcal cells will start proliferating in the lung granuloma and eventually will disseminate to the brain. Many investigators have sought to study the protective host immune response to this pathogen in search of host parameters that keep the proliferation of cryptococcal cells under control. The majority of the work assimilates research carried out using the primary infection animal model, mainly because a reactivation model has been available only very recently. This review will focus on anti-cryptococcal immunity in both the primary and reactivation models. An understanding of the differences in host immunity between the primary and reactivation models will help to define the key host parameters that control the infections and are important for the research and development of new therapeutic and vaccine strategies against cryptococcosis.